Factors Influencing SMEs’ Access to Finance in South Africa - Serame, Molobeng (Graduate School of Business (GSB), 2019)
Policymakers and scholars universally accept and recognise the influence of small, macro, and medium enterprises (SMMEs) on stimulating economic growth and job creation. South Africa in particular, has the challenge of a high unemployment rate, particularly among the youth, coupled with high inequality levels and stagnant economic growth over the recent years. These challenges have made the role of SMMEs even more important in South Africa. Despite the known importance of the influence of SMEs on the economy and the government initiatives to grow SMEs, SMEs continue to face challenges of access to finance and high failure rates in their start-up phases. Against this background, this study examined the key reasons SMMEs struggle to gain access to banking finance with the aim of understanding the root causes of those reasons. This study aimed to provide solutions to addressing the root causes of SMMEs inaccessibility to finance to narrowing the finance gap in this segment. The study employed the parallel convergent mixed methods approach that combined both qualitative and quantitative approaches in data collection and analysis. Convenient sampling was used to identify the SMMEs for quantitative research. The empirical evidence was collected using survey data. The survey was distributed among the SMMEs sampled. For qualitative research, purposeful sampling was used to identify the research participants. Four bank managers working specifically with SME finance were selected and approached for the research. Qualitative data was collected using semi-structured interviews. The study found that most SMMEs struggle to get access to finance with the majority citing a poor credit record as the main reason for being declined for credit. Most SMMEs are deterred from applying for banking finance and find the processes long and complicated. The study also found that the root cause of SMMEs low access to banking finance is a lack of education and understanding of bank processes and factors influencing their creditworthiness. These include poor governance by SMMEs and lack of proper bookkeeping. It is recommended that SMMEs upskill themselves with financial literacy and basic business management skills. Banks should find innovative ways of assessing creditworthiness for SMMEs and should consider other data sources. A collaboration between banks, government agents, and DFIs is advised.